Abdominal Circumference Alone versus Estimated Fetal Weight after 24 Weeks to Predict Small or Large for Gestational Age at Birth: A Meta-Analysis - Blue, Nathan R.; Yordan, José M. Pérez; Holbrook, Bradley D.; Nirgudkar, Pranita A.; Mozurkewich, Ellen L. (American Journal of Perinatology, 2017)
Objective We compared the sensitivity and specificity of abdominal circumference (AC) alone versus estimated fetal weight (EFW) to predict small for gestational age (SGA) or large for gestational age (LGA) at birth.Study Design We searched the literature for studies assessing an ultrasonographic AC or EFW after 24 weeks to predict SGA or LGA at birth. Case series or studies including anomalous fetuses or multiple gestations were excluded. We computed the sensitivity, specificity, and positive and negative predictive values of any AC or EFW cutoff analyzed by at least two studies.Results We identified 2,460 studies, of which 40 met inclusion criteria (n = 36,519). Four studies assessed AC alone to predict SGA (n = 5,119), and six assessed AC to predict LGA (n = 6,110). Sixteen assessed EFW to predict SGA (n = 13,825), and 22 evaluated EFW to predict LGA (n = 18,896). To predict SGA, AC and EFW < 10th percentile have similar ability to predict SGA. To predict LGA, AC cutoffs were comparable to all EFW cutoffs, except that AC > 35 cm had better sensitivity.Conclusion After 24 weeks, AC is comparable to EFW to predict both SGA and LGA. In settings where serial EFWs are inaccessible, a simpler screening method with AC alone may suffice.
Keywords: abdominal circumference; birth weight; estimated fetal weight; fetal growth restriction; large for gestational age; small for gestational age